Enhancing Interoperability: Exploring Data Exchange Standards in SaaS Laboratory Management Systems - Vuppalapaty, Vicrumnaug (Journal of Science & Technology, 2023)
In the ever-changing environment of health care, smooth information exchange among different systems is significant to ensure efficiency and high-quality patient care. This is also important in laboratory management, where time and accuracy are critical for patients’ diagnosis and treatment choices. Nevertheless, interoperability is still a big issue, with SaaS laboratory systems being the primary concern. This study focuses on the importance of interoperability in contemporary healthcare systems, with particular emphasis on laboratory management. It shows the significance of an uninterrupted data flow between SaaS laboratory management systems and other healthcare I.T. systems, such as E.H.R.s and HIEs. Existing data exchange standards and frameworks for interoperability among SaaS laboratory management systems are discussed, including the challenges of achieving interoperability. A quantitative research approach-based questionnaire was deployed to assess the interoperability requirements and processes of the genetic testing laboratories in the survey. Investigations point to different levels of compatibility among SaaS lab management systems in terms of features offered as well as the challenges faced by the latter. Challenges include different data formats, communication protocol standards, and data model incompatibility. The study emphasizes the critical role of interoperability and data exchange in SaaS laboratory management systems and the entire healthcare industry. The methods of overcoming the interoperability problem are investing in education, creating collaborative partnerships, promoting integration frameworks, and establishing incentives for obedience to standardized data exchange format.